Eksistensi Model Perguruan Tinggi di Lingkungan Pondok Pesantren (Studi Tentang Peluang dan Tantangannya di Era 4.0) - Mustopa Mustopa; Ahmad Hapidin; Jagad Rayana; Asep Deni Adnan Bumaeri; Hisam Ahyani (Sekolah Tinggi Agama Islam Sumatera Medan, 2021)
The model of higher education in Islamic boarding schools has indeed become something new in the dynamics of Islamic education. Its existence is even more dynamic in the midst of the 4.0 era, of course there are opportunities and challenges to be faced. This study aims to 1) analyze the model of higher education in the pesantren environment in implementing education in the 4.0 era. 2) analyze the strategies used by Islamic boarding schools to maintain the existence of universities. 3) analyze the opportunities and challenges faced by universities in the pesantren environment. The research method used is library research. The results of the study found that in the 4.0 era through various models offered in maintaining its existence, it was to strengthen management, governance, and human resources without losing the traditions, culture, curriculum in Islamic boarding schools that oversee certain universities. In addition, it can be done by making innovations in order to maintain the quality of higher education, such as the use of digital-based learning media for students. Opportunities that are owned are government policies that take sides, educational models that are in accordance with the demands of the times, qualified human resources. The challenges are the demands of technological developments, curriculum adjustments, and resisting change.